2021
DOI: 10.1002/anie.202105733
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Total Synthesis and Structural Revision of Dysiherbol A

Abstract: A 12‐step total synthesis of the natural product dysiherbol A, a strongly anti‐inflammatory and anti‐tumor avarane meroterpene isolated from the marine sponge Dysidea sp., was elaborated. As key steps, the synthesis features an enantioselective Cu‐catalyzed 1,4‐addition/enolate‐trapping opening move, an Au‐catalyzed double cyclization to build up the tetracyclic core‐carbon skeleton, and a late installation of the C5‐bridgehead methyl group via proton‐induced cyclopropane opening associated with spontaneous cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 70 publications
(51 reference statements)
2
27
0
1
Order By: Relevance
“…8). 55 Plakinidone (36) from the Caribbean sponge Plakortis angulospiculatus, was originally reported as the rst naturally occurring six-membered peroxylactone (Fig. 8) and showed mild antimicrobial activity.…”
Section: Reviewmentioning
confidence: 99%
“…8). 55 Plakinidone (36) from the Caribbean sponge Plakortis angulospiculatus, was originally reported as the rst naturally occurring six-membered peroxylactone (Fig. 8) and showed mild antimicrobial activity.…”
Section: Reviewmentioning
confidence: 99%
“…However, it was later found that the hydroxyl group at the C-4 position of the A ring and the hydroxyl group at the C-20 of the D ring (see Table 1 , entry 3) were fused to form a pentacyclic skeleton containing an ether bond. Subsequently, the Schmalz [ 17 ] and Liu [ 18 , 19 ] groups individually synthesized the confirmed structure of dysiherbol A for the first time, although different synthetic routes were employed.…”
Section: Examples Of Total Synthesis Of Marine Natural Products Resul...mentioning
confidence: 99%
“…52 In this manner, we synthesized a variety of highly substituted indenes by reaction of 7-aryl cycloheptatrienes 47 and 1,2-disubstituted allenes 52, using a cationic gold(I) complex as catalyst (Scheme 25, top). This strategy allowed the preparation of indene intermediate 53e, which after elaboration through 5-6 more steps, led to the construction of the carbon skeletons of both the cycloaurenones and the dysiherbols, 53 two families of natural products featuring a cis-or trans-decalin core, respectively (Scheme 25, bottom). In contrast, we found that if 7-styryl cycloheptatrienes 54 are used as carbene precursors, the same allenes react to give cyclopentadienes 55 (Scheme 26).…”
Section: (3+2) Cycloadditions Of Au(i) Carbenesmentioning
confidence: 99%